2021
DOI: 10.1002/adfm.202101428
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Mechanical Metamaterials with Programmable Quasi‐Zero‐Stiffness Features for Full‐Band Vibration Isolation

Abstract: Quasi‐zero‐stiffness (QZS) isolators of high‐static‐low‐dynamic stiffness play an important role in ultra‐low frequency vibration mitigation. While the current designs of QZS mainly exploit the combination of negative‐stiffness corrector and positive‐stiffness element, and only have a single QZS working range, here a class of tailored mechanical metamaterials with programmable QZS features is proposed. These programmed structures contain curved beams with geometries that are specifically designed to enable the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…The design of structures displaying a prescribed force-displacement response is a challenge in the engineering of mechanical metamaterials [25,36,42,44]. An important example of such a device is the force-limiter, used to prevent unbounded growth of a force applied to a sensitive element.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of structures displaying a prescribed force-displacement response is a challenge in the engineering of mechanical metamaterials [25,36,42,44]. An important example of such a device is the force-limiter, used to prevent unbounded growth of a force applied to a sensitive element.…”
Section: Introductionmentioning
confidence: 99%
“…Stability character of the non-trivial configurations and snap motion towards them have been assessed through the numerical solution of the nonlinear dynamic equations (43) and(44).…”
mentioning
confidence: 99%
“…One is to devise the mechanical structure to decrease the stiffness, and the other is to adjust the stiffness real-time. Introducing the negative stiffness mechanism [67,82] , decreasing the cross-section of the elastic material [56][57][83][84] , and adjusting the amount of compression [71][72]74,85] are the mechanical ways to change the resonator stiffness. Although these mechanical structures are in favor of obtaining band gap in the low-frequency range, these configurations are difficult to change once they were designed.…”
Section: Band Gap Tuning Based On Adjustable Stiffnessmentioning
confidence: 99%
“…Ruan et al provided a type of spiral phononic crystal for the low-frequency isolation on a ship [21]. Zhang et al reported a type of tailored Mechanical metamaterial with programmable quasi-zero-stiffness features for full-band vibration isolation [22]. Wu et al proposed a kind of mechanical metamaterials, which can circulate the energy between the metamaterial and the energy source, without passing energy to the payload [14].…”
Section: Introductionmentioning
confidence: 99%